Transnational corporations and transnational banks as international business parties - Макарчук, Катерина (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism)
The article investigates the concept and key elements of the activity of transnational corporations and transnational banks as as international businessparties under the new conditions that exist of the world economy. The largest world TNCs and TNBs are examined. The features that characterize contemporary TNCs and TNBs are revealed. The article analyses development of TNCs and TNBs cooperation within international business.